Desvelando a periferia: ficção e história em Capão Pecado, de Ferréz - Fin, Claudia Cristina (My University, 2020)
This paper aims to analyze the representations of the periphery in the novel Capão pecado as a historical source from the fields of literary criticism and the historiographical current of New Cultural History (NCH) that defends the approximation between Literature and History. Ferréz?s novel, Capão pecado, as well as the authors other productions, is part of a cultural movement that coined for itself the expression of "marginal literature", produced by writers from the periphery. The periphery and its entire orbit are the guiding thread of the novel, as well as the guiding thread of most of the works that make up this cultural movement. Social problems and their causal relationships with unfinished citizenship processes in Brazil lead the reader to reflect on the complexity of this place coined as periphery. When analyzing this literary text from the perspective of a historical source, it will be sought to show how literary creation can unveil the social gaps still latent in Brazilian society today [resumo fornecido pelo autor].
Este trabalho tem por objetivo analisar as representações da periferia no romance Capão pecado, de Ferréz, como fonte histórica, partindo dos campos da crítica literária e da corrente historiográfica da Nova História Cultural (NHC) que defendem as aproximações entre Literatura e História. Esta obra de Ferréz, assim como as demais produções do autor, está inserida dentro de um movimento cultural que cunhou para si a expressão de "literatura marginal", produzida por escritores da periferia. A periferia e toda a sua órbita são o fio condutor do romance, bem como de grande parte das obras que compõem esse movimento cultural. Problemáticas sociais e suas relações de causalidade com os processos de cidadania inconclusos no Brasil conduzem o leitor a refletir sobre a complexidade desse lugar cunhado como periferia. Ao analisar esse texto literário pela perspectiva de fonte histórica, busca-se evidenciar como a ficção literária pode desvelar os abismos sociais ainda latentes na sociedade brasileira atual [resumo fornecido pelo autor].
Keywords: Literatura brasileira - Ficção - Crítica e interpretação; Marginalizados na literatura; Periferia; Ferréz, 1975-; Brazilian literature - Fiction - Criticism and interpretation; Outcasts in literature; Inner cities